Spectral correction for handheld optoacoustic imaging by means of near‐infrared optical tomography in reflection mode. Issue 1 (2nd October 2018) - Ulrich, Leonie; Ahnen, Linda; Akarçay, Hidayet Günhan; Majos, Salvador Sánchez; Jaeger, Michael; Held, Kai Gerrit; Wolf, Martin; Frenz, Martin
Abstract : In vivo imaging of tissue/vasculature oxygen saturation levels is of prime interest in many clinical applications. To this end, the feasibility of combining two distinct and complementary imaging modalities is investigated: optoacoustics (OA) and near‐infrared optical tomography (NIROT), both operating noninvasively in reflection mode. Experiments were conducted on two optically heterogeneous phantoms mimicking tissue before and after the occurrence of a perturbation. OA imaging was used to resolve submillimetric vessel‐like optical absorbers at depths up to 25 mm, but with a spectral distortion in the OA signals. NIROT measurements were utilized to image perturbations in the background and to estimate the light fluence inside the phantoms at the wavelength pair (760 nm, 830 nm). This enabled the spectral correction of the vessel‐like absorbers' OA signals: the error in the ratio of the absorption coefficient at 830 nm to that at 760 nm was reduced from 60%‐150% to 10%‐20%. The results suggest that oxygen saturation ( SO 2 ) levels in arteries can be determined with <10% error and furthermore, that relative changes in vessels' SO 2 can be monitored with even better accuracy. The outcome relies on a proper identification of the OA signals emanating from the studied vessels. Abstract : Optoacoustics (OA) is combined with near‐infrared optical tomography (NIROT) in reflection mode to quantitatively image vasculature oxygen saturation ( SO 2 ) levels in phantoms containing vessels at depths up to 25 mm. Using NIROT to estimate the light fluence, the OA signals' spectral distortion was reduced from 60%‐150% to 10%‐20%. Results suggest that SO 2 levels can be determined with <10% error and that temporal changes can be monitored with even better accuracy.